2015
DOI: 10.1111/vru.12241
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Lesions and Lameness in 121 Horses With Carpal Sheath Effusion (1999–2010)

Abstract: Equine carpal sheath effusion has multiple etiologies. The purpose of this retrospective study was to describe the prevalence of distinct musculoskeletal lesions lameness in a sample of horses with a clinical diagnosis of carpal sheath effusion. A total of 121 horses met inclusion criteria. Seventy-four percent (89/121) of horses were lame at presentation; middle-aged (9-18 years, 80%) and older (> 18 years, 85%) horses were lame more frequently than young horses (< 9 years, 44%). Ninety-three percent (113/121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Pathologies affecting the carpal sheath have been recognized in horses for decades. However, large case series have not been reported until recently, and new pathological entities affecting the region continue to be recognized and described . This situation is likely a reflection of the low prevalence of carpal sheath pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pathologies affecting the carpal sheath have been recognized in horses for decades. However, large case series have not been reported until recently, and new pathological entities affecting the region continue to be recognized and described . This situation is likely a reflection of the low prevalence of carpal sheath pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is likely a reflection of the low prevalence of carpal sheath pathologies. Jorgensen et al reported that only 2% to 3% of new ultrasounds per year are performed because of problems suspected within the carpal sheath. Thus, it is likely that the anatomic knowledge and diagnostic capabilities of most equine veterinarians are lower for the carpal sheath than for other regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C arpal region is a compound part of the thoracic limb with various structures incorporated carpal joint, ligaments, tendons and muscles (Getty, 1975;Dyce et al, 2009). Carpal joint may be subjected to many pathological changes related to the joint structures, ligaments, tendons of the carpal region (Magnusson and Ekman, 2001;Malone et al, 2003;Vaughan et al, 2014;Jorgensen et al, 2015;Shields et al, 2015).…”
Section: Introductionmentioning
confidence: 99%